2022
DOI: 10.1158/1078-0432.ccr-21-3023
|View full text |Cite
|
Sign up to set email alerts
|

Olaparib Maintenance Monotherapy in Asian Patients with Platinum-Sensitive Relapsed Ovarian Cancer: Phase III Trial (L-MOCA)

Abstract: Translational StatementOlaparib, a poly (ADP-ribose) polymerase inhibitor, has shown encouraging efficacy in patients with platinum-sensitive relapse (PSR) ovarian cancer (OC) in global Phase III trials. However, evidence in the Asian population is lacking. In this Phase III, open-label, single-arm trial, olaparib maintenance monotherapy was highly effective and well tolerated in Asian patients (>90% Chinese) with PSR OC, regardless of their BRCA status. These results reinforce the current global evidence and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…An updated median OS of 32.7 months at a median follow-up of 33.1 months for the phase IIIb OPINION study was published at the 2022 ESMO Annual Meeting; the Kaplan-Meier analysis showed OS rates of 65.8% and 54.9% at 24 and 30 months, respectively, and these data further support the use of olaparib maintenance therapy for the treatment of non-gBRCAm PSROC (Poveda Velasco et al, 2022). The L-MOCA study was the first clinical study to assess the efficacy and tolerability of olaparib maintenance treatment in Asian PSROC patients, and an mPFS Frontiers in Pharmacology frontiersin.org of 16.1 months for all patients as of 25 December 2020, was reported (Gao et al, 2022). Subgroup analysis showed that compared to the corresponding wild-type group mPFS, the BRCA mutation group mPFS (21.2 months vs 11.0 months) and the HRR mutation group mPFS (18.3 months vs 13.3 months) were better.…”
Section: Second-line and Beyond Treatment With Olaparibsupporting
confidence: 56%
See 1 more Smart Citation
“…An updated median OS of 32.7 months at a median follow-up of 33.1 months for the phase IIIb OPINION study was published at the 2022 ESMO Annual Meeting; the Kaplan-Meier analysis showed OS rates of 65.8% and 54.9% at 24 and 30 months, respectively, and these data further support the use of olaparib maintenance therapy for the treatment of non-gBRCAm PSROC (Poveda Velasco et al, 2022). The L-MOCA study was the first clinical study to assess the efficacy and tolerability of olaparib maintenance treatment in Asian PSROC patients, and an mPFS Frontiers in Pharmacology frontiersin.org of 16.1 months for all patients as of 25 December 2020, was reported (Gao et al, 2022). Subgroup analysis showed that compared to the corresponding wild-type group mPFS, the BRCA mutation group mPFS (21.2 months vs 11.0 months) and the HRR mutation group mPFS (18.3 months vs 13.3 months) were better.…”
Section: Second-line and Beyond Treatment With Olaparibsupporting
confidence: 56%
“…The AE incidence was 99.1%, with the most common AE being anemia (76.4%), and 9.4% of patients discontinued treatment due to treatment-related AEs. This study showed that in Asian PSROC patients, olaparib maintenance therapy had significant efficacy regardless of BRCA status and was well tolerated by patients (Gao et al, 2022). In 2014, the Food and Drug Administration (FDA) approved olaparib in this population based on the results of Study 42 (NCT01078662), in which patients with recurrent gBRCAm OC who had received at least three chemotherapy regimens responded durably to olaparib (Figure 1) (Domchek et al, 2016).…”
Section: Second-line and Beyond Treatment With Olaparibmentioning
confidence: 89%
“…In the phase IIIb OPINION trial (NCT03402841) (Poveda et al, 2022), maintenance olaparib demonstrated clinical benefit in patients without a germline BRCA1/BRCA2 mutation (gBRCAm). Additionally, the phase â…˘ trial L-MOCA (NCT03534453) (Gao et al, 2022) ) has demonstrated that PARP inhibition is also an effective treatment for patients with metastatic breast cancer with gPALB2 (ORR, 82%) and sBRCA1/2 (ORR, 50%) mutations, significantly expanding the population of breast cancer patients who may benefit from PARPi, indicating that not only gBRCA1/ 2 mutation carriers, but also other mutations in homologous recombination-related genes may benefit from PARPi (Tung et al, 2020). Likewise, according to an article published in the Lancet Oncology July 2022 (NCT03404960), PARPi combined with nivolumab or niraparib has shown effectiveness among pancreatic cancer patients, even though the BRCA mutation rate in pancreatic cancer is only about 4%-7% (Reiss et al, 2022).…”
Section: Current Approved Parp Inhibitorsmentioning
confidence: 99%
“…In the phase IIIb OPINION trial (NCT03402841) ( Poveda et al, 2022 ), maintenance olaparib demonstrated clinical benefit in patients without a germline BRCA1/BRCA2 mutation (gBRCAm). Additionally, the phase â…˘ trial L-MOCA (NCT03534453) ( Gao et al, 2022 ), focused on olaparib maintenance monotherapy in Asian patients with platinum-sensitive relapsed (PSR) ovarian cancer has been published this year. As the first study to aim at the efficacy and tolerability of olaparib that specifically for Asian patients with PSR ovarian cancer, it highlights the promising efficacy of olaparib in Asian population.…”
Section: Current Approved Parp Inhibitorsmentioning
confidence: 99%
“…We present the case of a 56-year-old woman with histologically proven primary ovarian cancer who suffered from three recurrences and four line therapies (Figure 1). She participated in the AICE trial 9 and L-MOCA trial 10 , and provided a written informed consent. These two study protocols were both approved by the ethics committee of Zhongshan Hospital, Fudan University (Approval number: B2014-117, B2018-068R).…”
Section: Case Reportmentioning
confidence: 99%